Efficient Utilization of Degraded Lands for Green Biomass Production Through Silvi-pastoral System in Doon Valley - Singh, Charan (Indian Forester, 2010)
The study was conducted during 1990 to 2000 in the subtropical climate on degraded bouldery riverbed land containing 74% of bouldery contents. The five treatments were compared with two tree canopy management practices along with Napier grass and without grass. The G. optiva did not affect the survival and growth parameters significantly and the highest grass survival (78.6%) was recorded under the tree pollarding management practice followed by grass alone without tree association (72.5%). The maximum green biomass production (260 q/ha) from Napier was recorded under Pollarding followed by total tree biomass from Pollarding alone (89 q/ha). The total biomass from the silvipastoral system as a whole was highest with pollarding + grass (296 q/ha), followed by lopping + grass (229 q/ha). Therefore, the pollarding + grass (management) association was the best treatment to obtain maximum grass biomass from degraded lands.